When Tragedy Strikes: Potential Contributions From Ocean Observation to Search and Rescue Operations After Drowning Accidents - Mateus, Marcos; Canelas, Ricardo; Pinto, Ligia; Vaz, Nuno (Frontiers in Marine Science, 2020)
Drowning accidents followed by the disappearance of the body are particularly distressing events. When such tragedy strikes, Search and Rescue Operations are usually deployed to recover the body. The efficiency of such efforts can be enhanced by timely data and appropriate data integration tools, such as operational prediction systems relying on numerical models or other data sources. In this paper, we propose four stages for Search and Rescue Operations after drowning accidents and briefly address the critical role of ocean observations at each stage, as well as the relevancy of available computational resources. The potential of the combination of different data sources on the state of the sea to provide better insight into Search and Rescue Operations is discussed. This work is a challenge to oceanographers, data scientists and relevant marine stakeholders to produce knowledge and tools to support Search and Rescue Operations after drowning accidents.